Pengaruh Lingkungan Kerja Serta Keselamatan Dan Kesehatan Kerja Terhadap Kinerja Karyawan Bagian Produksi Pada PT. Sari Sentana Arka - Syariffudin, Machrup; Parma, I Putu Gede (Universitas Pendidikan Ganesha, 2020)
This study aimed to obtain explanative findings about the effect of (1) working environment on employee’s performance, (2) occupational safety and health on employee’s performance, (3) working environment on employee’s occupational safety and health, and (4) working environment on employee’s performance through Occupational Health and Safety. The research design used in this study was a causal quantitative research design. The subjects of this study were all production department employees at PT. Sari Sentana Arka. The population of this research was 32 people. Data were collected using questionnaire technique to obtain the data about the working environment, occupational safety and health and employee’s performance. Data were analyzed using path analysis. The results showed that: (1) the working environment had a significant effect on employee’s performance, (2) occupational safety and health had a significant effect on employee’s performance, (3) the working environment had a significant effect on occupational safety and health, and (4) the working environment had a significant effect on employee’s performance through occupational safety and health.